PELAKSANAAN SUPERVISI AKADEMIK PENGAWAS SEKOLAH DALAM MENINGKATKAN KINERJA GURU SEKOLAH DASAR DI KOTA DUMAI - Asniarny Asniarny (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research is motivated by poor teacher performance. For this reason the aim of this research is to improve teacher performance by carrying out academic supervision. This study uses a school action research design that has stages of planning, implementation, observation, reflection. This research was conducted at the target schools in Dumai city from March 4 to April 27. The subjects of this study were grade IV elementary school teachers totaling 11 people. Data analysis instruments use observation sheets that are analyzed and described according to the criteria set. The results showed that the teacher's performance in the first cycle had an average percentage of 65% with sufficient criteria, classically the number of teachers who achieved the indicator of success was 3 people (27%). After repairs with academic supervision, the performance of teachers in the second cycle increased with a percentage of 81% with sufficient criteria. Classically the number of teachers who achieved good performance was 9 people (81%). The conclusion of this study is the implementation of academic supervision can improve the performance of elementary school teachers in the city of Dumai.